2009
DOI: 10.1007/s00424-009-0683-x
|View full text |Cite
|
Sign up to set email alerts
|

Defining features of the hair cell mechanoelectrical transducer channel

Abstract: This review summarizes current knowledge of the hair cell mechanotransducer channel, the ion channel responsible for detecting mechanical stimuli in the inner ear and one of the few channels whose molecular structure is still unknown. Several candidate proteins have been proposed, especially members of the transient receptor potential (TRP) channel family, but all have so far failed in one test or another. Furthermore, none has biophysical properties exactly matching the native channel. The defining features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 73 publications
3
58
1
Order By: Relevance
“…Similarly, interaction of QX-314 with permeating monovalent ions can explain the sidedness with which it acts, with inward current flow by monovalents effectively displacing internally applied QX-314 from its binding site, so that it blocks only outward current, and similarly for outward current flow displacing externally applied QX-314. The ability of QX-314 and large quaternary ammonium molecules to act as permeant blockers in TRPV1 is reminiscent of the behavior of large permeant blockers like the cationic antibiotic dihydrostreptomycin in the hair cell mechanoelectrical transducer (MET) channel, another large-pore channel (Farris et al 2004;Fettiplace 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, interaction of QX-314 with permeating monovalent ions can explain the sidedness with which it acts, with inward current flow by monovalents effectively displacing internally applied QX-314 from its binding site, so that it blocks only outward current, and similarly for outward current flow displacing externally applied QX-314. The ability of QX-314 and large quaternary ammonium molecules to act as permeant blockers in TRPV1 is reminiscent of the behavior of large permeant blockers like the cationic antibiotic dihydrostreptomycin in the hair cell mechanoelectrical transducer (MET) channel, another large-pore channel (Farris et al 2004;Fettiplace 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the screen revealed TRPP3 and PKD1L3 RNA expression patterns that were correlated with the acquisition of sensory transduction in outer hair cells (Lelli et al, J Neurophysiol. 101:2961-2973, 2009). Numerous spatiotemporal expression gradients were identified many of which may contribute to the normal functional development of the mouse cochlea.…”
Section: Introductionmentioning
confidence: 99%
“…Sound-induced deflection of a hair bundle in the direction of the longest stereocilia stretches the tip link, thus opening the MET channel and initiating mechanotransduction (18,19,51). In the vertebrate inner ear, hair bundles are bathed in endolymph in which resides high K ϩ , and mechanotransduction is predominantly activated by K ϩ entry through MET channels (18, 65).…”
mentioning
confidence: 99%
“…Sound-induced deflection of a hair bundle in the direction of the longest stereocilia stretches the tip link, thus opening the MET channel and initiating mechanotransduction (18,19,51). In the vertebrate inner ear, hair bundles are bathed in endolymph in which resides high K ϩ , and mechanotransduction is predominantly activated by K ϩ entry through MET channels (18,65). However, electrophysiological analysis of isolated hair cells showed that MET channel is a nonselective cation channel with high Ca 2ϩ permeability, which passes Ca 2ϩ at least fives times better than it does Na ϩ and K ϩ (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation